Pengaruh Media Ular Tangga PGS terhadap Pengetahuan, Sikap, dan Praktik Gizi pada Siswa Sekolah Dasar: The Influence of PGS Snakes and Ladders Media on Knowledge, Attitudes, and Nutritional Practices in Elementary School Students - Rahayu, Rahmayanti; Setiawan, Budi (Jurnal Ilmu Gizi dan Dietetik, 2025)
One of the efforts in conveying the message of balanced nutrition is by providing nutrition education using interactive media to enhance knowledge, attitudes, and practices of balanced nutrition. This study aims to analyze the influence of the PGS snakes and ladders media on knowledge, attitudes, and nutrition practices among elementary school students. The research design used is quasi-experimental with a one-group pretest-posttest, conducted in August-October 2024 at SDN Carangpulang 02 and SDN Tenjosari. The majority of subjects in the acceptance level group really liked the PGS Snakes and Ladders media (88.0%). The results of the difference test on the nutritional knowledge aspect showed a significant difference before and after the intervention (p<0.05). The results of the difference test on the nutritional attitude aspect showed no significant difference before and after the intervention (p>0.05). The aspects of nutritional practices and dietary diversity score show significant differences (p<0.05).